A STUDY OF CODE-SWITCHING OF TEACHER TALK ON TRAINEE TEACHER IN PPL II PROGRAM OF STATE UNIVERSITY OF SURABAYA (RETAIN, 2014)
A STUDY OF CODE-SWITCHING OF TEACHER TALK ON TRAINEE TEACHER IN PPL II PROGRAM OF STATE UNIVERSITY OF SURABAYA Renata Kenanga Rinda 10020084019 English Education, Faculty of Languages and Art, State University of Surabaya email: renata.rinda195@gmail.com Dosen Pembimbing: Prof. Dr. Hj. Lies Amin Lestari, M.A, M.Pd English Education, Faculty of Languages and Art, State University of Surabaya Abstrak Terdapat perbedaan pandangan tentang penggunaan alih kode dalam bahasa guru pada pengajaran bahasa Inggris sebagai bahasa kedua. Di satu sisi, bahasa Inggris sangat dianjurkan untuk digunakan sebagai bahasa satu-satunya dalam mengajar, namun teori lain justru mengusulkan penggunaan beberapa bahasa sebagai alat guru dalam mengajarkan bahasa Inggris. Menanggapi masalah tersebut, penelitian ini dilakukan untuk mengetahui jenis-jenis bahasa, jenis-jenis alih kode, dan alasan penggunaannya yang dilakukan oleh calon guru pada PPL II, Universitas Negeri Surabaya. Catatan lapangan dan rekaman digunakan untuk mengumpulkan data yang diperlukan dalam penelitian deskriptif kualitatif ini. Hasil penelitian menunjukkan bahwa ada tiga jenis bahasa yang digunakan oleh calon guru; Bahasa Inggris, Indonesia, Jawa, dan Arab, dengan tiga jenis alih kode; tag-switching, inter-sentential switching, dan intra-sentential switching. Hasil penelitian juga mengungkapkan lima alasan penggunaan alih bahasa yaitu sebagai alat untuk mengajar, member penegasan, mengkritik, menyemangati, dan menanyakan hal kepada siswa yang membantu calon guru dalam mengelola kelas. Berdasarkan hal tersebut, dapat disimpulkan bahwa hasil penelitian ini mendukung teori kedua yang menganjurkan penggunaan beberapa bahasa dalam pengajaran bahasa Inggris sebagai bahasa kedua. Kata Kunci: mengajar bahasa Inggris sebagai bahasa kedua, bahasa guru, alih kode. Abstract The practice of code-switching in teacher talk for the teaching of English as second language exposed a contradictive theory about it. On the one hand, English was strongly proposed as the only language to be used while other theories allow the use of various languages as medium of instruction implemented used as the teacher’s equipment in managing the classroom. Coping with the above dilemma, this research aimed at investigating the types of languages, types of code-switching, and reasons of using them in trainee teacher's teacher talk in PPL II program of State University of Surabaya. Field notes and audio recording were employed in five observations to confirm the data revealed under the descriptive qualitative research. The findings pointed out that there were four types of languages used in trainee teacher's teacher talk; English, Bahasa Indonesia, Javanese, and Arabic, with three types of code-switching; tag switching, inter-sentential switching, and intra-sentential switching. The findings also described five reasons of using code-switching; lecturing, giving directions or confirmation, criticizing or justifying authority, praising or encouraging, and asking question toward the students which helped the trainee teacher managed the class. In sum, the result of this study supported the second theory which allows the use of various languages in teaching English in second language classroom. Keywords: teaching English as a second language, teacher talk, code-switching introduction Reinforcing the Indonesia’s competitiveness as a member of the developing nations, the demand to improve people’s education level is enormously needed. Then, to cope with it, teachers as the foremost stakeholder in this area have the biggest role to settle on whether the improvement can be achieved or not. This fact is agreed as a general truth for the reason that the students’ enhancement in the class is most impacted by the teachers (McCaffrey, Lockwood, Koretz, Louis, & Hamilton, 2004). As a result, this reality becomes a powerful foundation for the Government to construct a shifting rule in education policies. Several policies are made, then the most significant one is the lecturers and teachers regulation that is called UU No. 14/2005, short of Undang-Undang Republik Indonesia Nomor 14 Tahun 2005 Tentang Guru dan Dosen. Basically, it has three major points stated; the general rules of teachers, teachers’ competences and qualifications, and then the obligations and rights of the teachers. The three of them go in certain directions which make the system of education enhanced through the development of the teachers’ quality. Fulfilling the above goal, the policy regulates some criteria that teachers should have; pedagogical, personality, professionalism, and social competences. Indeed, realizing the four criteria mentioned is not an effortless task to deal with. The Government will not be able to reach it without working hand in hand with other components in the education world. Under this consideration, the Government calls for shot to the education institutions to prop up the new policy. One of the umbrella institutions that gets the mandate is State University of Surabaya that has main responsibility to educate the undergraduate students who take education as their major of study. Regarding to the Government’s requirements, State University of Surabaya tries to bring them into reality through a program named PPL, stands for Program Pengalaman Lapangan consisting of PPL I and PPL II. Consequently, all of the students in Education Department, State University of Surabaya, which is English Department, have to participate in both programs. In materializing those programs, in the sixth semester, the English Education Department conducts PPL I program carried in the campus to train the undergraduate students through microteaching activity. After that, the PPL II program starts on the seventh semester. This program held in the real teaching environment in several schools chosen for approximately three months long. This makes PPL II different from PPL I. Among several schools selected by the English Education Department, SMP Negeri 1 Madiun is one of them. In this school, there were four English undergraduate students who practiced teaching in the academic year of 2013. They had conscientiousness to manage the classroom in the seventh grade as real teachers. Based on the informal observation toward those trainee teachers, it was found that all of them tried to handle the class by using English. They greeted the students, delivered the material, and even responded to the questions by utilizing the same language. This special language used by the trainee teachers to address the students in English classroom is called teacher talk (Ellis, 1985). Moreover, teacher talk turns out to be a major resource of the students related to their language input (Al-Otaibi, 2004). By giving good model through their talk, it is hoped that students can get good example in practicing English. Understanding this theory, the trainee teachers in SMP Negeri 1 Madiun were in the right track to keep implementing English in their talk. By giving the proper model of applying English, the students were expected to do the same. Nonetheless, the implementation of teacher talk of trainee teachers by using English in the seventh grade of SMP Negeri 1 Madiun was not supported well. Many students’ responses came up beyond the expectation. When the classroom atmosphere was packaged in all English, most students got confused and frustrated. They neither understood some words nor comprehend the teachers’ instructions. As a result; some students lost their attention to the trainee teachers. In order to cope with the unforeseen condition, the trainee teachers frequently changed their teacher talk into other languages such as Bahasa Indonesia or Javanese as alternative languages. These changing languages always happened automatically. In the first minute, the trainee teachers used English then suddenly changed it into Bahasa Indonesia or Javanese then got back into English. The three languages were used in one single sentence. In another occasion, the different pattern was found; sometimes the trainee teachers’ teacher talk was implemented in English while the class began, then in the middle of running the class, the use of Bahasa Indonesia was implemented then finally the trainee teachers closed their talk by reusing English. The above process of changing one language into other languages that happen in the middle of talk is called code-switching (Cook, 2000). The code-switching possibly involved in teacher talk is an unavoidable result of communication that happens among various languages circumstances. Moreover, because of code-switching in teacher talk is a special occurrence in teaching English, there are many analysis and theoretical discussions that are elicited in the previous decades (Gumperz, 1982). Several findings towards it spread out in the education world. Regarding to the above fact of code-switching language in teacher talk, it provided the underlying principle for undertaking this descriptive research, and which was initiated in a challenge to describe the types of languages, types of code-switching, and reasons of using them in trainee teacher’s teacher talk. Furthermore, by identifying them, it is expected that the findings of this research will be useful to draw the map of code-switching language that might happen in five or ten years later when the trainee teachers of PPL II program of English Education Department become a part of materializing the Indonesia’s education improvement as real teachers. METHODOLOGY Research Subjects Reflecting on the purposes of this research, it considered the three parameters in choosing the research subject; the status, the background language, and the achievement. The status of the subject observed was a trainee teacher. The researcher selected her rather than the real English teacher at that school since the trainee teacher observed right now would replace the position of the real teacher in conducting the second language classroom in the future. As a consequence, the research findings would be valuable information prepared for the trainee teacher before being a teacher. Then, the second reason was the language background. The trainee teacher and the students of SMP Negeri 1 Madiun, speak the same languages, it made the phenomenon of code-switching possibly appeared. Besides, the researcher considered the trainee teacher chosen for being a good model and achieving good GPA; 3, 57 within 0 – 4 scale. Instruments In this research, the field note observation and audio recording were utilized as the research instruments. By implementing the field note observation, it is possible to focus on the ongoing behaviors occur and note the most important feature in the classroom (Bailey, 1994). The model of field note was adapted from Konsep Penetian Tindakan Kelas dan Penelitianya. It consisted of four parts; identification, instruction, description material, and reflection material (Susanto, 2010). Then, the audio-recording was also employed as the second instruments to record the detail information appeared. Data Collection In collecting the data, five observations were conducted. Each observation took 2 sessions in 80 minutes. Moreover, the five observations were done in five weeks; four weeks on July and one week on August that were classified into two parts; direct informal observation and direct formal observation. Direct informal observation was conducted on the first week of August before running the formal one in order to know the basic information and condition of the subject observed in the classroom. Then, on the first, second, and third formal observations, the audio recording was placed on the nearest area of the trainee teacher in order to get the clearest sound. Then, the field note described the types of language, types of code-switching, and reasons of using them in the trainee teacher’ teacher talk on the description material. Next, the reflection material column was completed with the researcher’s point of view related to the case found. Last, while the fourth formal observation was completed, the researcher had to pay more attention toward the subject observed. Here, since the trainee teacher did not make any difference towards her types of languages, types code-switching used, and reasons of using them, the researcher could stop the observation. Data Analysis Types of Languages Related to the types of languages, the data found in the first observation were coded by “a”, second observation coded by “b”, and third observation coded by “c”. Then they were identified based on the four types of languages used; English, Bahasa Indonesia, Javanese, and Arabic. Those four types of languages were reclassified by the researcher based on the language combinations made by the trainee teacher namely first, English and Bahasa Indonesia, second, English and Javanese, third, English and Arabic, fourth, Bahasa Indonesia and Javanese, and last, English, Javanese, and Bahasa Indonesia. Types of Code-switching The types of code-switching were grouped based on Sankoff & Poplack (1981) namely tag-switching, inter-sentential switching, and intra-sentential switching. Moreover, the trainee teacher reclassified them concerning on the process involved; tag-switching were divided regarding on the simple fixed word insertion at the beginning and the end of code-switching, inter-sentential switching was reclassified into code switching between sentences or sentence and clause, and intra-sentential switching reclassified into word or phrase embedded in phrase or clause from another language, word or phrase inserted between words or phrases from another language, and words or phrase stayed between two types of languages. Reasons of using code-switching in teacher talk The reasons of using the code-switching in teacher talk made by the trainee teacher were identified based on Flanders (1970). There were seven categories which are lecturing, giving directions, criticizing or justifying authority, accepting feeling, praising or encouraging, accepting or using the students’ thought, and asking question towards the students. RESULTS Types of Languages After analyzing the field notes and audio recording transcriptions that were completed by the researcher on August 21st, August 28th, and September 4th, 2013, it was found that there were 211 code-switching used by the trainee teacher in her teacher talk. In those code-switching, four languages were used as the trainee teacher’s tool to accomplish the process of teaching English. Then, those four types of languages were reclassified by the researcher based on the language combinations made by the trainee teacher namely first, English and Bahasa Indonesia, second, English and Javanese, third, English and Arabic, four, Bahasa Indonesia and Javanese, and last, English, Javanese, and Bahasa Indonesia. The supporting facts quoted from the trainee teacher’s teacher talk related to the four languages found are provided in the following paragraphs. Firstly, the combination between English and Bahasa Indonesia languages contributed in three observations conducted. In the first observation, there were 53 code-switching composed by the two types of languages mentioned. Then, on the second observation it gained enlargement and reached 76 numbers. Last, it reduced slightly to 19 numbers on the third observation. Moreover, one of those examples was labeled by 1: (1) Student 18 :I will go to Mecca on May. Teacher :That’s enough. Sekarang mana Karina? Could you please tell me what is Azar’s plan on May? (1) Student 28 :He will go to Mecca. Teacher :On May, he will go to Mecca, repeat it. The code-switching marked by 1 was the example of the code-switching that used English and Bahasa Indonesia combination. At that time, the trainee teacher wanted student 18 namely Azar to tell his plan on May. After hearing Azar’s plan, the trainee teacher asked another student that was student 28, Karina, by first implementing the code-switching that was stated in Bahasa Indonesia, “Sekarang mana Karina?” to call her and then followed by English sentence stated in interrogative form,” Could you please tell me what is Azar’s plan on May?” Then, related to the reason of using it, the trainee teacher did the code-switching for asking question toward student 28 in order to tell what student 18 planned on May. Another example of this combination was also found in the code-switching numbered by 2: (2) Student 1 :Silent. Teacher :No? Why? You still have no idea? Okay, I will play the video again and listen. (Playing the video). You all must know how to tell time. What is the importance of telling time? This is the answer. So, what do you think about it? I need to learn telling time because I need to know time to go to school for example. What else? What else? Seperti yang disebutkan di video tadi (2). Students : Silent. Teacher :I need to telling time because? Anyone? Anyone? Aga? Through the above example, the existence of English and Bahasa Indonesia were also clearly seen. Firstly, the trainee teacher asked the students about the importance of the material given. Since the students were not able to answer the trainee teacher’s question, she delivered her question again. Then, she finally answered her own question in order to show the students how to deal with it On the contrary; the students were silent and gained no movement. Moreover, related to this example, the code-switching was used. English came first then followed by Bahasa Indonesia. Then, the unique thing appeared in this example was when the trainee teacher switched her talk from English to Bahasa Indonesia, there was also English word insertion “video” in the middle of Bahasa Indonesia sentence. Next, in line with its function, through this code-switching, the trainee teacher tried to give confirmation about the answer of the question mentioned before. Then, the second combination involved the two types of languages which were English and Javanese, also recorded in the three observations conducted but the combination was only found in one number for each. The trainee teacher did this second combination in 3: (3) Students :Doubt . . . climbing. (Repeating the teacher) Teacher :Yes, right. Student 13 :ndaut . . .ndaut (Speaking in Javanese) Teacher :No, it is different. Ndaut is an activity which is usually done by the farmer, right? (3) At this point, the word ndaut taken from Javanese came first then followed by English. This code switching was implemented when the trainee teacher taught the pronunciation of the word doubt. The trainee teacher lectured the students in correct way by saying /daƱt/. Otherwise, the students made fun of it and preferred to pronounce doubt as ndaut since they had already known and more familiar with this Javanese word comparing to English. For that reason, the trainee teacher commented on the students’ pronunciation by criticizing them by delivering code-switching containing English and Javanese language. Then, the second example related to the same combination was stated in 4: (4) Student 15 :Raising her hand. Teacher :Okay. Student 15 :We need to know time to have breakfast. Teacher :Okay, we need to know what time to have breakfast. And then? Heh, sorry, what is your name? (4) At this point, the trainee teacher had a discussion with the students about the importance of telling time. When the students wanted to share their idea about it, they had to raise their hands then the trainee teacher gave them a score by marking their name list. The trainee teacher used the code-switching to call the student by mentioning him in Javanese word heh to replace the student’s name since she did not know yet. Then, it was followed by a question formed in English. By implementing this code-switching, the trainee teacher used it as a tool for asking question to the student. Next, the third combination was comprised from English and Arabic language. This language combination was only found in the second observation in one number. It was supported by the code-switching labeled 5: (5) Student 3 :Balik ke Surabaya kapan? Teacher :Insyaalloh, I will back to Surabaya at September, 15 (5). Guys, on September 14, my friends and I will have a surprise for all of you Students : Apa? Surprise? This code-switching appeared while the students asked when the trainee teacher would back to her college in Surabaya. In answering the students’ question, she implemented an Arabic word insyaallah that was commonly used in Indonesia even though most of Indonesians do not speak Arabic well. Moreover, it was used as a mark of certainty related to the future plan as cited in,” “Insyaallah, I will back to Surabaya at September, 15.” The Arabic word was stated first then an English sentence formed in the future tense mentioning the exact date of the trainee teacher’s leaving. Through this point, it could be observed that the trainee teacher used code-switching as the teacher’s tool for giving a confirmation for a certain case. The fourth combination was the only one that did not contain English in it. It was composed from Bahasa Indonesia and Javanese that appeared on three numbers in the second observation and one in the third observation. The example was labeled by 6: (6) Teacher :Kamu tahu kata kerja bentuk pertama? Student : . . . . . (silent) Teacher :Kata kerja pertama itu gak enek embel-embel e (6). Students : Ohh . . . At first, Bahasa Indonesia was implemented, and then it was switched to Javanese language in gak enek embel-embel e. Moreover, by delivering this code-switching, the trainee teacher lectured her students in defining the verb used for telling the daily activities. She said, the verb one should not be added by –ed or –ing that the students usually made mistakes on. Another example of the same language combination mentioned in 7: (7) Teacher :Begini, kita di sini dinilai sama guru pamong. Guru pamongnya siapa? Bu Pur. Student 8 :Yang bahasa Inggris itu? Teacher :He em, guru angkat yang di sini. Ibu angkat yang di sini (7) Student 32 : Brarti tinggalnya di mana? Similarly, the trainee teacher implemented Bahasa Indonesia first, and switched to Javanese then. Nevertheless, in 7, the trainee teacher used the code-switching to give confirmation toward the student 8’s question by saying he em in order to express her agreement with the student’s statement. The last combination happened among English, Javanese, and Bahasa Indonesia. This combination was comprised from three types of languages that did not appear on the first and second observation but finally used in one number in the third observation. It was labeled by 8: (8) Student 21 :Masih bingung, Miss Teacher :Okay. Verb one do not contain embel-embel apapun. Gak enek embel-embel apa-apanya. Hanya bentuk dasar, okay (8). Firstly, English was used to mention the case that the trainee teacher explained, then Javanese appeared in the middle of the sentence, and finally it was ended by the code-switching to Bahasa Indonesia. The trainee teacher used this code-switching to answer the students’ question related to the correct form of the verb that should be used in making a sentence based on the picture given on the slide show. Since there were many students got confuse, the trainee teacher chose to explain the case by implementing Javanese and Bahasa Indonesia in order to make the students get a clear understanding. Through the above descriptions in connection with the types of languages in the three weeks observations that were conducted in row, in short, the trainee teacher did the code switching in her teacher talk by utilizing four languages by implementing five combinations. In addition, the trainee teacher preferred to use the first combination of English and Bahasa Indonesia comparing to the other four combinations namely English and Javanese, English and Arabic, Bahasa Indonesia and Javanese, and English, Javanese, and Bahasa Indonesia that only appeared in less than three numbers. Types of Code-switching In terms of the types of code-switching used, three observations that were conducted by the researcher gave the same results. Then, they were grouped based on Sankoff & Poplack (1981); tag-switching, inter-sentential switching, and intra-sentential switching. Tag-switching was the easiest type of code-switching that could be identified. Its characteristic which is the insertion of simple fixed word from one language in a sentence from another language becomes a valuable sign in marking this code-switching’s type. Moreover, there were 60 tag-switching found during the observations; 18 of them used in the first observation, 26 in the second observation, and 16 in the third observation. They created two different patterns related to the simple fixed word place of insertion. The first pattern was the simple fixed word insertion embedded at the beginning of the sentence. As it was stated in 9: (9) Student 21 :Miss, saya? Teacher :Tunggu, Budi duluan. Come on Budi, kamu bisa Budi (9). Kamu bisa, ini sangat gampang. Come on as part of English simple fixed word was inserted at the beginning of code-switching then was followed by Bahasa Indonesia language. At that time, the trainee teacher wanted Budi to come forward and tell his assignment in front of his friends. On the contrary, the student did not give any response and kept silent. Dealing with it, the trainee teacher encouraged the student by saying “come on” then did automatic changing language by switching her talk to Bahasa Indonesia. As a result, Budi participated in the classroom activity and showed his ability in presenting the assignment. Another example of this pattern was also mentioned in 10: (10) Teacher :Can I borrow it? Just for showing the slide show. Just for showing the slide show. Student 23 :Giving his laptop. Teacher :Okay, thank you. Sorry, something goes wrong with the laptop. Sorry. Just be quite while waiting me to set the laptop. Just wait. Do not make any noise. Just wait. Just wait. The laptop is error. Sorry. Just wait. Just wait. We will still continue the lesson. Nah, it should be like this (10) Comparing to the previous question, in this tag-switching, the simple fixed word was formed in Bahasa Indonesia nah. Then, related to its function, the trainee teacher tried to give a confirmation related to the picture projected from the laptop. However, the code-switching that was labeled by 10 still had the same pattern with the previous one. Another tag-switching that had different pattern related to the position of the simple fixed word insertion was observed in 11: (11)Students : . . . . . . . . (making noise) Teacher :I won’t start if you are still making noise. Anyone, hello boys over there back to your seat please. I won’t start the lesson if you still make noise, sudah? (11) Students :Sudah. Teacher :Okay, anyone, do you remember what we did in last lesson? Do you still remember what we did last lesson? In this tag-switching, sudah was inserted in the end of the sentence. It was contradictive with the previous pattern that the simple fixed word used at the beginning of the tag-switching. In 11, sudah was spoken in Bahasa Indonesia that was embedded in the English sentence. Moreover, concerning to its function, by delivering this code-switching the trainee teacher justified her authority in controlling the classroom situation since there were many students who kept busy in their talking when the lesson started. After delivering this tag-switching, the trainee teacher started the classroom activities when the situation was not too noisy. Then, not only found in 11, the second pattern of tag-switching also observed in 12: (12)Student 4 :Great time? Teacher :Great time has the same meaning with very happy. Mereka sangat bahagia setiap kali mereka berkumpul, clear? (12) Students :Yes. In 12, the trainee teacher spoke in Bahasa Indonesia first, then, she switched her talk to English by mentioning a simple fixed word “clear”. Through this example, the trainee teacher used the same pattern of tag-switching as shown in 11 but it had different reason which was asking question toward the students’ understanding. Besides the above examples, other simple fixed words found were eight in English; okay, sorry, right, hello, please, now, guys, and stop, and three in Bahasa Indonesia; ya, siapa, and jangan. All of them created the same pattern with the two examples explored which were either embedded at the beginning or at the end of the tag-switching. After investigating the existence of tag-switching, the second types of it namely inter-sentential switching was also implemented by the trainee teacher. There were 92 inter-sentential switching used by the trainee teacher during her teaching; 25 found in the first, 36 in the second, and 31 in the third observation. Generally, it happened in two patterns which were first, inter-sentential switching between sentences and second, inter-sentential switching between sentence and clause. The trainee teacher did inter-sentential switching between two sentences in 13: (13)Teacher :Okay, could you please continue your plans? Student 25 :I will visit Bandung on January. Teacher: Now, Rio. What is Granta’s plan on January? Gak usah tanya yang lain (13). Student 26 :He will . . . The utterances in 13 were composed by two sentences, first sentence formed in all English and then it was followed by the second sentence stated in Bahasa Indonesia. The trainee teacher changed her talk after finishing her full sentence in one language first, and then stated the sentence in different language. This reason made it classified into inter-sentential between two sentences. Next, concerning on the function of this switching, at this time, the trainee teacher wanted student 28 to answer her question about student 25’s plan on January. To elicit the student, the trainee teacher directed a question to him. Another example of inter-sentential switching between two sentences also used in 14: (14)Student 5 : Ya ampun angel e. Teacher :Contohnya seperti tadi ya. Just make piece of paragraph or writing. Caranya gampang kan, seperti tadi. (417) Student 5 :Ini dikumpulkan? The example showed that the trainee teacher mentioned the sentence in Bahasa Indonesia that was switched to English then returned to Bahasa Indonesia. This inter-sentential switching turned up when the trainee teacher wanted to give confirmation to the students related to the assignment given which was about creating a simple paragraph. Showing the different pattern, inter-sentential switching used between sentence and clause was found in 15: (15)Teacher :Just say the tree is okay, but tree of hopes is also okay because your tree contains of so many hopes so you can say the tree of hopes. Student 9 :Opo? Opo? Teacher :The tree is okay. The tree of hopes is okay. Because almost of all of these contain your hopes. That is okay. I give the name “the tree” or “the tree of hopes” karena pohonnya banyak sekali mengandung harapan-harapan kalian (15). The English sentence was spoken first and then followed by clause in Bahasa Indonesia. Here, the English sentence could actually stand by itself without any clause followed. However, in this case, the clause spoken in Bahasa Indonesia was used as an extended reason for the preceding sentence. As a consequence, it made the existence of inter-sentential switching between sentence and clause clearly seen. Moreover, through this switching, the trainee teacher gave a confirmation toward the title of the assignment given that the students asked. Also, the pattern of inter-sentential switching was observed in 16: (16)Students :Discussing and continuing their tree of hopes with their friends. Student 4 :Kalau pengen lihat Sakura di Jepang? Teacher :I will visit Japan to see the beautiful Sakura. Seperti ini nanti, on January I will visit France. (16) Bahasa Indonesia clause seperti ini nanti was stated just before the English sentence. Here, the trainee teacher used it as a tool to lecture the students about how to write down their plan for each month. Last, the analysis of the third type of code-switching which is intra-sentential switching found in 59 numbers. Starting from the first to the last observation, the number of intra-sentential switching was decreasing. There were 10 numbers found in first, then 20 numbers in the second, then reached up to 12 in the last observation. Furthermore, the present of intra-sentential switching can be observed when there is an insertion of word or phrase embedded in phrase stated in another language inside the sentence boundary. There were three patterns found contributed in intra-sentential switching. First pattern of intra-sentential switching is a phrase or word that was embedded into another phrase or clause formed in different language. This pattern was mentioned in 17: (17)Teacher :Apa ini pentingnya? Kenapa harus mempelajari ini? Kenapa kita harus mempelajari telling time? (17). Student 3 :Silent. Teacher :Ada yang tahu? On the above situation, the trainee teacher implemented intra-sentential switching by using Bahasa Indonesia to ask the students about the importance of the material given, Kenapa kita harus mempelajari . . . However, she still stated the theme of the lesson by inserting English phrase “telling time” at the end of the sentence that made the existence of intra-sentential switching used. By implementing this intra-sentential switching, the trainee teacher was able to make the students answer the question she asked about. The second example of the same pattern of intra-sentential switching labeled by 18: (18)Teacher :Jadi seperti itu, kalau misalkan kalian menggunakan ekspresi I wish (18). Contohnya seperti itu. Okay? Students : Yes. In the 18, the trainee teacher lectured the students by implementing tag-switching that happened between Bahasa Indonesia clause and an English phrase. The trainee teacher put her effort in order to explain the material given to the students by using this intra-sentential switching. Then, the second pattern is a word or phrase inserted in the middle of other words or phrases from another language. This pattern was stated in 19: (19)Teacher :Do you have another question? Student 9 :Kalau merayakan ulang tahun temen itu apa, Miss? Teacher :I will celebrate my friend’s birthday. My friend pake apostrophe (19). Student 32 :Miss? Miss? The word pake which was taken from Bahasa Indonesia was inserted by the trainee teacher in between English phrase and word. My friend and apostrophe enclosed it on either side, therefore, pake was placed in the middle of them. Moreover, by delivering this intra-sentential switching, the trainee teacher lectured the students related to the lesson given. She informed the students about the use of apostrophe as a possessive noun mark that the students confused. Then, the same pattern of intra-sentential switching also supported by 20: (20)Teacher :To give me a new mobile phone. HP itu mobile phone. (20) Okay? Student 3 :Miss, kalau punya banyak permintaan? Teacher : I have a lot of . . . Here, the word taken from Bahasa Indonesia also stayed in between the two English words. Here the trainee teacher used it to give a confirmation to the students that hand phone is just the same with the mobile phone. Next, the third pattern of intra-sentential switching happened among several words in three languages in one sentence. This pattern appeared only in 8: (21)Teacher :Kata kerja pertama itu gak enek embel-embel e. Student :Ohh . . . Student 21 :Masih bingung, Miss Teacher :Okay. Verb one do not contain embel embel apapun (8). This intra-sentential switching was contributed by three types of languages; English, Javanese, and Bahasa Indonesia. It made the third type different from the two previous examples that were only composed from two types of languages. Furthermore, the word embel-embel, which was stated in Javanese, was inserted by the trainee teacher in between English phrases and Bahasa Indonesia word. This intra-sentential switching was delivered by the trainee teacher when she lectured the students about present tense. At that time, the students commonly made mistakes related to the form of verb that should be used in present tense. As a consequence, the trainee teacher gave them further understanding toward the case by saying intra-sentential switching in 8. After describing the types of code-switching used in trainee teacher’s teacher talk, in summary, there were three types of them used in teaching foreign language classroom. They were tag-switching marked by the existence of simple fixed at the beginning or the end of the code-switching, inter-sentential switching identified from its composition between sentences or sentence and clause, and intra-sentential switching that used through word or phrase embedded in phrase or clause from another language, word or phrase inserted between words or phrases from another language, and words or phrase stayed in between two types of languages. DISCUSSION Related to the types of languages contributed on the code-switching done by the trainee teacher in her teacher talk, the implementation of various languages in the second language classroom was proven. The results pointed out the four types of languages; English, Bahasa Indonesia, Javanese, and Arabic that were reclassified by the researcher into five combinations based on the language combinations made by the trainee teacher. They were English and Bahasa Indonesia, English and Javanese, English and Arabic, Bahasa Indonesia and Javanese, and English, Javanese, and Bahasa Indonesia. They were used by the trainee teacher in running the second language classroom of the seventh grade in SMP Negeri 1 Madiun. Since the trainee teacher used various types of languages, it can be said that teaching English as a foreign language will not be able to be separated with the practice of other languages that both trainee teacher and students acquired before. Also reflecting on the same facts, the trainee teacher mostly used the first combination which was English and Bahasa Indonesia stated on 203 numbers in three observations recorded. Then, the others combinations only contributed in few numbers; English and Javanese appeared in 3 times, English and Arabic in once, Bahasa Indonesia and Javanese in twice, and last combination, English, Javanese, and Bahasa Indonesia in once only. Regarding to this fact, among the five combinations found, the trainee teacher preferred to use the first one among the others. Having compared to the theory of teaching English in the second language classroom, the trainee teacher’s decision for applying various languages but still put English as the preferable language used among the others was on the correct track. It is believed since the implementation of English provides the language input for the students when there is a very limited support from the other resources (Stern, 1983). This condition was represented by the teaching English as a second language in the seventh grade of SMPN 1 Madiun. The students were lack of resources since English was only used in the English classroom. Then, concerning on the second research question, which was the types of code-switching used, there were three types of them were used in teaching second language classroom based on Sankoff & Poplack (1981). They were tag-switching marked by the existence of simple fixed at the beginning or the end of the code-switching, inter-sentential switching identified from its composition between sentences or sentence and clause, and intra-sentential switching used through word or phrase embedded in phrase or clause from another language, word or phrase inserted between words or phrases from another language, and words or phrase stayed in between two types of languages. Among the three types of code-switching used, inter-sentential switching was most implemented. The use of it was found in 25 numbers in first observation, then it became higher in the second observation which covered 36 numbers, then it decreased slightly in the last observation, 31 numbers. Then, in the second rank was tag-switching found in 60 numbers. In the first observation, it appeared on 18 numbers then enlarged up to 26 in the second observation then finally decreased to be 16 numbers in the third observation. Last, the fewest type of code-switching used was intra-sentential switching that was found in 59 numbers. Ten of them were implemented in the first observation then increased in the second observation and reached up to 12 numbers in the last observation. Referring to the theory in teaching English as a second language, the implementation of code-switching was also allowed to do. It is believed since the use of code-switching becomes an alternative way that can be utilized in bilingual or multilingual circumstances (Auer, 1998). Since English was taught as a foreign language in Indonesia, both teacher and students acquired their first language first. In this case, Bahasa Indonesia, Javanese, and Arabic were languages they spoke before. This reason caused the code-switching made by the trainee teacher composed of the four languages. Conversely, if both teacher and students did not live under the bilingual or multilingual circumstances, they would not have been able to speak various languages then the implementation of code-switching would not be there. Also, by implementing the first language, the process of acquiring the second language which was English would be considered as a successful process since both teacher and students understood the different things about them (Faerch & Kasper, 1983). When the code-switching was implemented, the English was not the only language that was allowed to be used. Here, both first language and English were used together. Through this practice, the understanding about their differences could be clear. For example, in 3, the trainee teacher described the differences between doubt and ndaut. The first word was taken from English while the second one was from Javanese. They both did not have any correlation related to their meaning. In order to make the students understand about them, the trainee teacher used both words in English and Javanese. The third point, in line with the reasons of using the code-switching in teacher talk reflected on Flanders (1970) which are lecturing, giving directions or confirmation, criticizing or justifying authority, accepting feeling, praising or encouraging, accepting or using the students’ thought, and asking question towards the students. Among the seven reasons mentioned, only five of them became the reasons why the trainee teacher used code-switching in her talk when teaching English as foreign language was done. They were lecturing the students, giving confirmation, criticizing or justifying the authority, praising and encouraging, and asking question. Based on the above discussions, related to the types of languages and code switching done by the trainee teacher in her teacher talk, both of them were not deniable to be implemented since it revealed five positive reasons of using them. However, the use of English as a foreign language should be maximized in order to give a comprehensible input for the students. CONCLUSIONS Regarding to the results revealed in this study, it exposed the four conclusions related to the research questions discussed. First, related to the types of languages used by the trainee teacher in her teacher talk, there were four types of languages English, Bahasa Indonesia, Javanese, and Arabic represented on the five combinations namely English and Bahasa Indonesia, English and Javanese, English and Arabic, Bahasa Indonesia and Javanese, and English, Javanese, and Bahasa Indonesia. Second, there were three types of code-switching which were tag-switching, inter-sentential switching, and intra-sentential switching in five combinations namely English and Bahasa Indonesia, English and Javanese, English and Arabic, Bahasa Indonesia and Javanese, and English, Javanese, and Bahasa Indonesia. Third, there were five reasons of using the code-switching in teacher talk which were lecturing, giving directions or confirmation, criticizing or justifying authority, praising or encouraging, and asking question towards the students. REFERENCES Al-Otaibi, S. S. H. (2004). The Effect of "Positive Teacher Talk" on Students' Performance, Interaction & Attitudes: A case Study of Female Students at the College of Languages & Translation at King Saud University. King Saud University, King Saud. Ary, D., Jacobs, L. C., & Sorensen, C. (2010). Introduction to Research in Education. Belmont, CA: Wadsworth. Auer, P. (1998). Code-switching in Conversation: Language, Interaction and Identity London: Routledge. Bailey, K. D. (1994). Methods of Social Research (4 ed.). New York: The Free Press. Cook, V. (2000). Second Language Learning and Language Teaching (2 ed.). Beijing: Foreign Language Teaching and Research Press. Ellis, R. (1985). Understanding Second Language Acquisition. Shanghai: Foreign Language Education Press. Faerch, C., & Kasper, G. (1983). ‘Plans and strategies in foreign language communication’, in Strategies in Interlanguage Communication. London: Longman. Flanders, N. A. (1970). Analyzing Teacher Behavior. Addison-Wesley: Reading Mass. Gumperz, J. (1982). Discourse Strategies. Cambridge: Cambridge University Press. McCaffrey, D. F., Lockwood, J. R., Koretz, D., Louis, T. A., & Hamilton, L. (2004). Models for the Value Added Modeling of Teacher Effects. Journal of Educational and Behavioral Statistics, 1. Sankoff, D., & Poplack, S. (1981). A Formal Grammar for Code-switching International Journal of Human Communication 14(Papers in Linguistics), 3-45. Stern, H. H. (1983). Fundamental Concepts of Language Teaching. Shanghai: Shanghai Foreign Language Education Press. Susanto. (2010). Konsep Penelitian Tindakan Kelas dan Penerapannya. Surabaya: Lembaga Penerbitan FBS UNESA.